AUSTRIAN BUSINESSMEN AND THE CAUCASIAN PETROLEUM INDUSTRY IN THE LATE 1800`S - EARLY 1900`S - Andrej N. Ptitsyn (Вестник Северо-Кавказского федерального университета, 2022)
The article considers participation of the Austrian businessmen and managers in development of a petroleum industry on Caucasus during the pre-revolutionary period.